(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The 2014 General Elections was a vote against the incumbent government and the reason behind it was lack of faith in the government’s political will and integrity. A series of corruption scandals had rocked the nation and the opposition was ready and armed with the opportunity to showcase their personal and political integrity case studies. The opposition convinced the Indian voters to oust the current government and bring them in with the promise of a beautiful vibrant democracy, corruption free India, a land of everyone’s dreams, a Ramrajya. We must, however, remember that such democratic changes are not short term but in fact a long term commitment requiring continuous and sustained effort. Also, any attempt to create a corruption free infrastructure is not possible by a one man army or any one political party. If we wish to create a vibrant democracy that is corruption free, transparent and accountable, we need to have a holistic, all inclusive systematic and structured approach starting with our political institutions. High cost of funding elections, with unaccounted for black money, has been a major factor behind corruption amongst all political parties for decades and unless this is changed, one of the major causes of corruption will go unaddressed. A vigilant and conscious population can play a significant role in fighting against corruption, by batting for a corruption free political leadership that is more accountable and transparent.